(untitled) (TAMADDUN NURI JURNALI, 2024)
This study examines the connection between Eastern dramaturgy and Uzbek theatre through the perspectives of thinkers, including Nizami, Bekhbudi, and Fitrat. Notable pioneers of Azerbaijani drama, such as M.F. Akhundov and G. Javid, play a significant role in this context. Special attention is given to G. Javid, whose works, such as "Sheyda", "Sheikh Senan", "Iblis", were successfully staged on the Uzbek stage in the 1920s. Research by scholars such as S. Aliyev and Sh. Turdyev underscores the broad popularity of G. Javid’s works among the Uzbek people. Archive data and testimonies of Uzbek artists also highlight the important role of Azerbaijani drama in shaping the Uzbek theatrical scene. Furthermore, the study reflects the influence of scholars and artists from Azerbaijan on the local theatrical and literary arts through their presence in educational institutions in Uzbekistan.`